PENGARUH MODEL THINK PAIR SHARE (TPS) BERBANTUAN WORDWALL TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN PENDIDIKAN PANCASILA PESERTA DIDIK KELAS V SD - Sherli Marsela; Dayu Rika Perdana; Tegar Pambudhi; Sowiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Think Pair Share (TPS) learning model assisted by Wordwall on the critical thinking skills of fifth-grade students in Pancasila Education subject. The main problem in this study is the low critical thinking ability of students caused by conventional learning that is still teacher-centered. The research method used a quasi-experimental design with a nonequivalent control group design. The research sample consisted of 37 students, comprising 19 students in the control class and 18 students in the experimental class, using saturated sampling technique. Data collection techniques were conducted through observation, documentation, and tests in the form of pretest and posttest. Data analysis employed normality test, homogeneity test, N-gain test, and simple linear regression test. The results showed that the Think Pair Share (TPS) learning model assisted by Wordwall has a significant effect on the critical thinking skills of fifth-grade students in Pancasila Education subject, with an F-value of 14.063 and a significance level of 0.001 (p < 0.05). The R Square value of 0.293 indicates that the TPS model assisted by Wordwall contributes 29.3% to students' critical thinking skills. The highest improvement occurred in the Inference indicator, with an N-gain of the experimental class at 0.45, higher than the control class at 0.32.